IMPLEMENTATION OF SCHOOL MANAGEMENT INFORMATION SYSTEM IN ENHANCING ACADEMIC SERVICES (A Case Study at Tunas Bangsa Excellent Public High School) - Nur Aidar; Hizir; Ismail (CV. RADJA PUBLIKA, 2024)
The rapid growth of information technology in recent years has also impacted all institutions, including educational institutions such as schools. As a system expected to enhance educational services, the function of management information systems involves formal activities in collecting, processing, and disseminating information to individuals within an organization. The purpose of this research is to provide an overview of the implementation of a school management information system in enhancing academic services at Tunas Bangsa Excellent Public High School. The focus of this research is: 1) How data collection of the school management information system improves academic services at Tunas Bangsa Excellent Public High School, 2) How data processing and storage of the school management information system enhance academic services at Tunas Bangsa Excellent Public High School, 3) What are the obstacles in implementing the school management information system to enhance academic services at Tunas Bangsa Excellent Public High School, 4) How the school management information system is utilized to enhance academic services at Tunas Bangsa Excellent Public High School. This research was conducted qualitatively using a case study research design. Data collection techniques included interviews, observations, and documentation. Data validity was ensured through careful observation and triangulation testing. The subjects in this study included the school principal, vice principal for student affairs, administrative staff, and school operators. Findings from the research are as follows: (1) Data collection of the school management information system to enhance academic services at Tunas Bangsa Excellent Public High School is conducted through the website program and the e-Report application program, (2) Data processing and storage of the school management information system to enhance academic services at Tunas Bangsa Excellent Public High School are still not optimal because some menu options on the website cannot fully utilize their data, (3) Obstacles in implementing the school management information system to enhance academic services at Tunas Bangsa Excellent Public High School include insufficient resources to implement the system, (4) Factors supporting the utilization of the school management information system to enhance academic services at Tunas Bangsa Excellent Public High School include human resources, facilities, the website, and the specialized e-Report application.